Beauty Queens and Wallflowers : Currency Unions in the Middle East and Central Asia - Elborgh-Woytek, Katrin (IMF Working Papers; Working Paper ;, 2006)
Against the background of the theory of optimum currency areas, the paper analyzes possible sequences for establishing a currency union (CU) in the Middle East and Central Asia region. Between the corner solutions of independent currencies for all countries in the region and a CU comprising all countries, a large number of combinations of member countries in the CU is possible. The analysis aims to determine the composition of potential CUs as a function of the country initiating the CU, an exogenously determined number of currencies in the region, and the weight attached to the particular selection criteria. Within this framework, the study seeks to establish whether some countries are consistently selected at early stages of the process, while others join only at later stages.